Analisis Pengaruh Literasi Keuangan Dan Sosial Media Edukasi Saham Terhadap Keputusan Investasi (Studi Kasus Pada Mahasiswa Kota Malang) - Muhammad Panji Wicaksono; Novi Lailiyul Wafiroh (Universitas Mataram, 2022)
The Research is conducted to analyze the effect of financial literacy and education on social media stocks on investment decisions in Malang city students. This type of research is quantitative with a descriptive approach. The population in this study is Malang city students who have social media accounts and also have an interest in investing, with a sample of 100 respondents. The sampling method used in this research is non-probability sampling with convenience sampling technique. Data collection techniques using a questionnaire distributed to the object of research. A data analysis technique uses the smartPLS3.0 application. Results showed that the variables of financial literacy and education on social media stocks had a positive and significant effect on investment decisions. In addition, the variables of financial literacy and social media education affect 57% while the remaining 43% are influenced by other variables